Class Imagery and Subjective Social Location During Iceland's Economic Crisis, 2008–2010. Issue 1 (2nd January 2018) - Oddsson, Guðmundur
ABSTRACT: It has long been argued that perceptions of the class structure shape how individuals see their position in society. However, researchers using nationally representative data to study subjective social location rarely include class imagery in their models. This study uses OLS regression of two surveys, conducted 18 months apart following Iceland's 2008 economic collapse, to analyze the effects of class imagery on subjective social location. Results show that respondents who perceive the class structure as inegalitarian report lower subjective social location as compared to those with egalitarian class imagery. The influence of objective class position on subjective social location depends, partly, on class imagery. The study finds that Icelanders saw the class structure become more egalitarian and their own subjective social location climb following the collapse, even as the economic crisis deepened between the two surveys. These findings reflect that income inequality in Iceland dropped sharply after the collapse.